Evidence‐Based Infection Control In Clinical Practice: If You Buy Clothes for the Emperor, Will He Wear Them?. (20th March 2013) - Morley, P.S.
Abstract : In the fabled story of the Emperor's New Clothes, nakedness is ignored, denied, and accepted despite its obviousness. Similarly, we seemingly have ignored, denied, and accepted the risks of healthcare‐associated infections (HCAI) in veterinary settings, despite common occurrence and obvious importance. Risks for HCAI in veterinary medicine cannot be denied and are increasingly apparent because of improved surveillance and reporting. We have an ethical responsibility to take all reasonable precautions to minimize foreseeable infectious disease hazards, and provide an environment in which personnel and patients are protected from infectious disease hazards so that care can be optimized. Yet, there is often a pronounced mismatch between what we know about risks for infectious disease and our actions. Veterinarians often fail to act on well‐known, universally accepted risks for infectious disease in patients and in people contacting these animals. We must educate personnel so they are well‐versed regarding agents commonly causing HCAI (including zoonotic infections), can identify patients with higher risks for shedding agents and for developing HCAI, have awareness of which procedures and management practices are associated with higher rates of HCAI, and have skill in applying effective prevention methods. We need to develop standardized benchmarks for risks of HCAI in veterinary settings, better understand efficacy and cost‐effectiveness for prevention practices, and develop good educational materials that will promote an effective understanding of risks and prevention methods for HCAI among personnel and the public. We need to buy new clothes for the emperor and be sure he actually wears them!